1997
DOI: 10.1530/eje.0.1360296
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor receptors in normal and tumorous adult human adrenocortical glands

Abstract: We have identified and characterized insulin-like growth factor (IGF)-I and IGF-II/mannose-6-phosphate (IGF-II/M6P) receptors in normal adult human adrenocortical tissue. Furthermore, we investigated the IGF-I receptor concentration and binding characteristics in benign and carcinomatous adrenocortical tumors. Membrane preparations of 14 normal adrenocortical glands showed a mean specific 125I-IGF-I binding (SB) of 5.0 +/- 0.5% and a competition by unlabeled ligands which is characteristic of the IGF-I recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 36 publications
5
71
0
3
Order By: Relevance
“…Here we show that the IGF-II (and not the IGF-I) gene is strongly expressed in H295R cells as in malignant human adrenocortical tumors (Ilvesmäki et al 1993, Gicquel et al 1994. We also show that IGF-II mRNAs are efficiently translated, with accumulation of IGF-II protein in culture media during cell proliferation, partly as precursor forms, as we previously showed in frozen adrenocortical carcinomas (Boulle et al 1998 (Weber et al 1997) but the expression of the IGF-II M6P receptor in adrenocortical tumors has only been studied at the mRNA level; RT-PCR has been used to show that the gene is expressed both in normal and tumorous adrenals (Ilvesmäki et al 1993).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Here we show that the IGF-II (and not the IGF-I) gene is strongly expressed in H295R cells as in malignant human adrenocortical tumors (Ilvesmäki et al 1993, Gicquel et al 1994. We also show that IGF-II mRNAs are efficiently translated, with accumulation of IGF-II protein in culture media during cell proliferation, partly as precursor forms, as we previously showed in frozen adrenocortical carcinomas (Boulle et al 1998 (Weber et al 1997) but the expression of the IGF-II M6P receptor in adrenocortical tumors has only been studied at the mRNA level; RT-PCR has been used to show that the gene is expressed both in normal and tumorous adrenals (Ilvesmäki et al 1993).…”
Section: Discussionsupporting
confidence: 77%
“…IGF-II mRNA is efficiently translated and malignant tumors contain large amounts of IGF-II protein, partly as precursor forms (Boulle et al 1998). IGF-I and IGF-II receptors are present in adrenal tissues and overexpression of the type 1 IGF receptor has been shown in adrenocortical carcinomas (Kamio et al 1991, Ilvesmäki et al 1993, Backlin et al 1995, Weber et al 1997. These previous studies all used frozen tumor tissues and give strong evidence for a role for IGF-II in adrenocortical tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, IGF-I and IGF-IR were detected in 80% to 100% and 92% of undifferentiated/poorly differentiated thyroid tumors (39), respectively; 67% to 100% and 50% to 100% of follicular thyroid cancers (39,40,43); 39% to 100% and 42-95% of papillary thyroid cancers (39,40,43); 80-100% and 50% of medullary thyroid cancer (46); 57% and 71% of pheochromocytomas (38); and 90% and 75% to 94% of adrenocortical cancers (38,41 Our results show that gastrinomas from different patients show a wide variation in the expression with IGF-I and IGF-IR mRNA levels. In follicular and papillary thyroid cancer, IGF-I and IGF-IR levels increases were reported of 2-to 7-fold, in adrenal cortical cancers IGF-IR was increased 3-to 5-fold (38), whereas in pancreatic cancer they were increased by 32-and 4.4-fold, respectively (34). Furthermore, our study showed a high significance (r = 0.66, P < 0.0001) between the level of expression of IGF-I and IGF-IR in a given gastrinoma.…”
Section: Igf-i and Igf-ir In Gastrinomasmentioning
confidence: 99%
“…receptors has been shown in ACC (69 (71). In ACC, only the maternal H19 allele is expressed, so expression of this gene is abolished in most ACCs displaying paternal isodisomy (62).…”
Section: Igf-ii and 11p15 Alterationsmentioning
confidence: 99%